2019
DOI: 10.1017/s0022215119002391
|View full text |Cite
|
Sign up to set email alerts
|

Impact of platelet-rich fibrin therapy in tympanoplasty type 1 surgery on graft survival and frequency-specific hearing outcomes: a retrospective analysis in patients with tympanic membrane perforation due to chronic otitis media

Abstract: ObjectiveTo evaluate the impact of platelet-rich fibrin therapy in tympanoplasty type 1 surgery on graft survival and frequency-specific hearing outcomes.MethodsPatients who underwent tympanoplasty type 1 surgery were randomised into temporal fascia graft alone (n = 55) and temporal fascia graft plus platelet-rich fibrin therapy (n = 36) groups. Graft survival and hearing outcomes were recorded.ResultsGraft survival rates were significantly higher in the temporal fascia graft plus platelet-rich fibrin therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…They concluded that PRF provides more rapid recovery, and better audiological improvement for acute traumatic perforation, compared to the paper patch method. Kütük compared the use of PRF plus temporalis fascia graft with temporalis fascia graft alone, and reported better graft survival rate in temporalis fascia graft plus PRF, similar hearing gain between groups 26 . In this study, the graft success rate in cartilage island graft with an extra perichondrium was 95.5%, while the graft success rate was 100% in the study group.…”
Section: Discussionmentioning
confidence: 60%
“…They concluded that PRF provides more rapid recovery, and better audiological improvement for acute traumatic perforation, compared to the paper patch method. Kütük compared the use of PRF plus temporalis fascia graft with temporalis fascia graft alone, and reported better graft survival rate in temporalis fascia graft plus PRF, similar hearing gain between groups 26 . In this study, the graft success rate in cartilage island graft with an extra perichondrium was 95.5%, while the graft success rate was 100% in the study group.…”
Section: Discussionmentioning
confidence: 60%
“…They used PRF as a plug over perforation sealed with temporalis muscle fascia and reported the superiority of PRF plugs in TM healing. Also, Kütük et al 6 reported the superiority of the PRF with temporal fascia graft compared to temporal fascia alone with better functional outcomes in their retrospective controlled study.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies reported better functional and surgical results in tympanoplasty with the use of PRP and PRF. 6 - 8 Plasma-derived platelet-rich biomaterials have encouraging results in tympanoplasty, and we believe that they can be an alternative to non-autologous materials. So, controlled clinical studies are mandatory to conclude their potential roles in otology.…”
Section: Introductionmentioning
confidence: 91%
“…Since the PRF is autologous, the chances of immunogenic reaction and graft failure are minimal. The process of preparing PRF is simple, quick, and cheap, does not increase the time of surgery and is also effective in wound healing and reduces the incidence of infections [ 3 , 13 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in ENT reported the use of PRF, particularly in ear surgery for repairing eardrum perforation [ 7 , 11 ]. PRF serves as a resorbable membrane that provides mechanical and inflammatory protection to the tympanic membrane [ 12 ], thereby improving the post-operative outcomes of ear surgery [ 13 ]. One of the advantages of PRF is its easy accessibility, allowing for unlimited utilization in myringoplasties, unlike the limited availability of cartilage, perichondrium, or temporalis fascia [ 14 ].…”
Section: Introductionmentioning
confidence: 99%